Eintrübung einer hydrophilen Intraokularlinse 4 Jahre nach Kataraktoperation: eine Biomaterialanalyse - Khoramnia, Ramin; Auffarth, Gerd U.; Schmidt, Stephan (Der Ophthalmologe, 2012)
Calcification of hydrophilic intraocular lenses (IOL) is a rare complication. We report about the uneventful replacement of an opacified hydrophilic IOL. The patient presented 4 years after uneventful cataract surgery with a reduction of visual acuity due to calcification of the IOL. Macroscopically, the optic and the haptics were opacified. Light and scanning electron microscopy revealed granular deposits on the external surface of the IOL and numerous fine granular deposits within the optic of the IOL which were distributed in a line parallel to the surface of the IOL.